A case study on the occurrence of polycyclic aromatic hydrocarbons in indoor dust of Serbian households: Distribution, source apportionment and health risk assessment. (May 2022) - Živančev, Jelena; Antić, Igor; Buljovčić, Maja; Đurišić-Mladenović, Nataša
Abstract: This study was conducted in order to obtain the first insight into the occurrence, potential sources, and health risks of polycyclic aromatic hydrocarbons (PAHs) in indoor dust. Samples (n = 47) were collected from households in four settlements in the northern Serbian province of Vojvodina. Total concentrations of 16 EPA priority PAHs in the dust samples varied from 140 to 8265 μg kg −1 . Mean and median values for all samples were 1825 and 1404 μg kg −1, respectively. According to the international guidelines for indoor environment, PAH content can be regarded as normal (<500 μg kg −1 ) for ∼6% of the samples, high (500–5000 μg kg −1 ) for ∼87% of the samples, and very high (5000–50000 μg kg 1 ) for ∼6% of the samples. In all settlements, PAHs with 4 rings were the most prevalent (accounting for 40–53% of the total PAHs). They were followed by 3-ringed PAHs (29–40%), which indicates rather uniform PAH profiles in the analyzed dust. Based on diagnostic ratios, principal component analysis (PCA), and positive matrix factorization (PMF), pyrogenic sources, such as vehicle emissions and wood combustion were the dominant sources of PAHs in analyzed samples. Health risk assessment, which included incidental ingesting, inhaling and skin contact with PAHs in the analyzed dust, was evaluated by using the incremental lifetime cancer risk (ILCR) model. Median total ILCR was 3.88E-04 for children, and 3.73E-04 for adults. Results revealed that major contribution to quite high total ILCRs was brought by dermal contact and ingestion. Total cancer risk for indoor dust indicated that 85% of the studied locations exceeded 10–4. This implies risk of high concern, with potential adverse health effects. The results are valuable for future observation of PAHs in indoor environment. They are also useful for regional authorities who can use them to create policies which control sources of pollution. Graphical abstract: Image 1 Highlights: Total PAHs in Serbian indoor environment varied in the range from 140 to 8265 μg kg −1 . 87% of analyzed dust samples were high contaminated (500–5000 μg kg −1 ). In all analyzed samples, PAHs with 4 rings were dominant, followed by 3-ringed PAHs. Fuel and wood combustion were assigned to be the dominant PAH sources. ILCR indicated that 85% of the studied locations were under the high risk.